Promoting Independent Sleep Onset in Young Children: Examination of the Excuse Me Drill. Issue 6 (1st November 2020) - Kuhn, Brett R.; LaBrot, Zachary C.; Ford, Ryan; Roane, Brandy M.
ABSTRACT: Background : There is compelling evidence to support behavioral interventions as the first-line approach for bedtime resistance in young children. Among the behavioral treatment options, extinction ("cry it out") has the most extensive empirical support and tends to produce the most rapid gains. There are well known problems with the use of extinction, however, including side effects (extinction burst, spontaneous recovery) and poor acceptance, not to mention that extinction fails to teach children appropriate replacement behaviors (what "to do"). This study introduces a new behavioral sleep intervention, the Excuse Me Drill, designed to address some of the limitations of extinction. The EMD was formally evaluated for the first time using a multiple-baseline research design across four participants with sleep disturbance.Participants : Participants included four children who were clinically referred to outpatient pediatric psychology clinics for the treatment of behavioral insomnia of childhood, and included one 2-year-old female, two 7-year-old females, and one 7-year-old male. All participants had a history of dependent sleep onset at bedtime (i.e., parents remained in the child's bedroom upon sleep onset). Methods : A non-concurrent multiple baseline design across participants was used to experimentally evaluate the effectiveness of the EMD. During baseline, parents collected data on independent sleep onset and disruptive bedtime behaviors, but conducted the bedtime routine as usual. Immediately following baseline, parents implemented the EMD protocol until data indicated that children were consistently initiating sleep independently. Follow-up data were collected to determine the extent to which children continued to initiate sleep independently at bedtime in absence of the EMD. Results : Outcomes were promising as the EMD successfully taught all four children to initiate sleep independently and produced notable decreases in disruptive bedtime behavior. Results were maintained at follow-up for three of four participants. In addition, parents rated the EMD to be a socially acceptable procedure for their children. Conclusions : Results of this study indicate that the EMD was effective in promoting independent sleep onset and reducing disruptive bedtime behavior that maintained over time. The EMD should be considered to be a viable alternative to traditional extinction procedures for pediatric sleep disturbance. Implications for practice, limitations, and direction for future research are discussed.